Voices That Care: Licensed Practical Nurses and the Emotional Labour Underpinning Their Collaborative Interactions with Registered Nurses - Truc Huynh; Marie Alderson; Michelle Nadon; Sylvia Kershaw-Rousseau (Nursing Research and Practice)
Recognizing the emotional labour underlying interprofessional collaborations (IPCs) could be considered a crucial step towards building a cohesive nursing team. Although IPCs between registered nurses (RNs) and licensed practical nurses (LPNs) have been linked to quality nursing care, little is known about the emotions experienced by LPNs during their interactions with RNs or those factors that influence IPCs. A questionnaire administered to 309 LPNs found that (1) the professional identity of LPNs has evolved into a that of a unique social group; (2) LPNs define IPC as an interpersonal process of exploring similar or dissimilar assessments of a patient's status with RNs and, together, establishing a course of nursing actions; (3) the primary organizational factor facilitating IPCs is inclusive nursing leadership; (4) the interpersonal factor promoting IPCs is the level of trust RNs extend to LPNs; and (5) an LPN's emotional labour (i.e., internal emotional regulation) is most tangible during uncollaborative interactions with RNs.